Communication in the Seventh Grade Classroom - Alfaro Rodríguez, Magdalena (2010)
Reflections on communication in the learning process at the level of the seventh year of secondary education based on the methodological and pedagogical approaches, considered in research of a multidisciplinary team of the CIDE of UNA (National University), with the aim of building the “teaching performance profile for the seventh year of Costa Rican education”. It demonstrates the role of teachers to ensure favorable communication links to the learning process, not only to capture the attention and interest of students through varied and systematic motivations, but also by the honesty, openness, personal example and involvement in the task, problems and aspirations of students.